The RNA Modification Database: 1999 update. - Rozenski, J (1999)
The RNA Modification Database (http://medlib.med.utah.edu/RNAmods/) provides a comprehensive listing of naturally modified nucleosides in RNA. Each file includes: chemical structure; common name and symbol; type(s) of RNA in which found and corresponding phylogenetic distribution; Chemical s registry number and index name; and initial literature citations for structure characterization and chemical synthesis. New features include capability to search database files by name or substructural features, modifications in tmRNA, and links to related data and sites.